Maladaptive Social Self-Beliefs in Alcohol-Dependence: A Specific Bias towards Excessive High Standards - Maurage, Pierre (Public Library of Science, 2013)
BACKGROUND: Emotional and interpersonal impairments associated with alcohol-dependence have been recently explored, but the distorted cognitive representations underlying these deficits remain poorly understood. The present study aims at exploring the presence of maladaptive social self-beliefs among alcohol-dependent individuals, as these biased self-beliefs have been recently shown to play a crucial role in the development and maintenance of other psychopathological states (social anxiety and depression). METHODOLOGY/PRINCIPAL FINDINGS: Twenty-five recently detoxified alcohol-dependent participants and 25 matched controls filled in self-report questionnaires evaluating maladaptive social self-beliefs, interpersonal problems and several comorbid states (anxiety, social anxiety, depression). As compared to controls, alcohol-dependent individuals showed higher scores than controls for the three subcategories of maladaptive social self-beliefs (high standards, conditional beliefs and unconditional beliefs). Our key finding was that when comorbidities were controlled for, alcohol-dependence was associated with a specific bias towards exaggerated high standards in social contexts. Moreover, these high standards beliefs were strongly correlated with interpersonal problems. CONCLUSIONS/SIGNIFICANCE: These results provide the first insights into the influence of cognitive biases on interpersonal problems in addictive states, and suggest that maladaptive self-beliefs could have a central influence on the development and maintenance of alcohol-dependence.